Internalization of Characters Through the Role Playing Method in Learning Short Stories (Case Study of SMPN 3 Cibatu Students) - Suharyanto H Soro; Nana Herdiana Abdul Rahman; Sri Rahmawati; Wilda Suryaningrat (Civiliza Publishing, Indonesia., 2025)
The low ability to tell short stories is one of the problems so that students tend to be rigid, lack confidence, and have difficulty expressing themselves emotionally. There is a gap between the demands of the curriculum that requires students to be skilled in communicative speaking and the reality in the field, showing that literary learning is still conventional and theoretical. This study aims to describe and analyze the internalization of characters through the Role Playing learning method in improving students' short story skills. The research paradigm used is qualitative with data collection methods in the form of non-participatory observations, limited interviews with teachers and students, and documentation. The findings of the study show that (1) The Role Playing Method is effective in building confidence so that it can create organic improvisation and natural gestures through the internalization of character characters; (2) Gestures and aspects of intonation, as well as articulation undergo changes through the process of imitation and creative sound experimentation; (3) Students no longer just memorize texts, but are able to bring the narrative to life through the synchronization of vocals and facial expressions. It was concluded that the Role Playing method succeeded in changing the storytelling learning paradigm from just an academic task to a creative form of self-actualization, improving the quality of storytelling, and successfully creating a supportive and appreciative classroom ecosystem.